2015
DOI: 10.1093/trstmh/trv016
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and clinical outcomes in patients with HIV on zidovudine and tenofovir based regimens: a retrospective cohort study

Abstract: Background: Adverse drug reactions are a major concern with zidovudine/stavudine treatment regimens. The less toxic tenofovir regimen is an alternative, but is seldom considered due to the higher costs. This study compared adverse drug reactions and other clinical outcomes resulting from the use of these two treatment regimens in India.Methods: Baseline, clinical characteristics and follow-up outcomes were collected by chart reviews of HIVpositive adults and compared using univariate/multivariate analysis, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…A total of 21 articles were included in this study: 10 observational cohort studies , six clinical trials , two cross‐sectional studies , one experimental study , one observational prospective study and one case report .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 articles were included in this study: 10 observational cohort studies , six clinical trials , two cross‐sectional studies , one experimental study , one observational prospective study and one case report .…”
Section: Resultsmentioning
confidence: 99%
“…Patients may therefore require periodic blood transfusion corresponding to clinical symptomatic state, but this is not without risks ranging from transfusion reactions and risk of other infections . The incidence of severe anemia in BU/HIV coinfection may also require that a first choice drug namely Zidovudine be replaced with Tenofovir as per protocol in most Sub‐Saharan regions . Tenofovir however is not readily stocked at most antiretroviral therapy (ART) centers at the sub‐districts and may pose serious treatment challenges .…”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
“…The incidence of severe anemia in BU/HIV coinfection may also require that a first choice drug namely Zidovudine be replaced with Tenofovir as per protocol in most Sub‐Saharan regions . Tenofovir however is not readily stocked at most antiretroviral therapy (ART) centers at the sub‐districts and may pose serious treatment challenges . In terms of effectiveness of drug therapy in BU/HIV coinfected cases, there are concerns about interaction between one of the first option ARTs (Nevirapine) and the antimycobacteria drug rifampicin, where it has been noted that the drug concentration of Nevirapine tends to decrease with such interactions …”
Section: Secondary Lesions Occurring After Bu Treatmentmentioning
confidence: 99%
“…A median delay of 5.5 days from the detection of HIV status to initiation of A.R.T was seen among the participants. A study by Thuppal et al 15 showed a median delay of 36 days with TDF regimen and 116 days with AZT based regimens. Incidence of ADRs accounted to 4.4 per person year and incidence of ADR reporting individuals to 123 per 100 person years.…”
Section: Resultsmentioning
confidence: 99%